SEDATIVE ACTIVITY OF THE CRUDE EXTRACT OF THE CRUDE EXTACT OF RAUVOLFIA DENSIFLORA - Weerakoon, S.W.; Arambewela, L.S.R.; Premakumara, G.A.S.; Ratnasooriya, W.D. (My University, 1998)
The sedative activity of Rauvollia densiflora Benth ex Hook. f. IApocynaceae) roots and leaves was evaluated using the rat hole board technique. The results indicate that crude extracts of R. densiflora has sedative properties as the leaf e.xtraci significantly reduced dips and rcarinii. and the root extracts reduced dips, motor and rearing activities related to exploratory behaviour of rats.